Multilayer MoS2 growth by metal and metal oxide sulfurization. Issue 6 (18th January 2016) - Heyne, M. H.; Chiappe, D.; Meersschaut, J.; Nuytten, T.; Conard, T.; Bender, H.; Huyghebaert, C.; Radu, I. P.; Caymax, M.; de Marneffe, J.-F.; Neyts, E. C.; De Gendt, S.
Abstract : The H2 S sulfurization of metal and metal oxide molybdenum films and the H2 influence on their morphology is described. Abstract : We investigated the deposition of MoS2 multilayers on large area substrates. The pre-deposition of metal or metal oxide with subsequent sulfurization is a promising technique to achieve layered films. We distinguish a different reaction behavior in metal oxide and metallic films and investigate the effect of the temperature, the H2 S/H2 gas mixture composition, and the role of the underlying substrate on the material quality. The results of the experiments suggest a MoS2 growth mechanism consisting of two subsequent process steps. At first, the reaction of the sulfur precursor with the metal or metal oxide occurs, requiring higher temperatures in the case of metallic film compared to metal oxide. At this stage, the basal planes assemble towards the diffusion direction of the reaction educts and products. After the sulfurization reaction, the material recrystallizes and the basal planes rearrange parallel to the substrate to minimize the surface energy. Therefore, substrates with low roughness show basal plane assembly parallel to the substrate. These results indicate that the substrate character has a significant impact on the assembly of low dimensional MoS2 films.